Investigating intention to receive the COVID-19 vaccine and willingness to pay among the general public in Pakistan - Ali Hassan Gillani, Wenjing Ji, Sumaira Omer, Sadia Bashir, Hafsa Arshad, Jamshaid Akbar, Kamran Bashir, Huda Abbas, Azzah Khadim Hussain (Journal of Applied Pharmaceutical Science, 2022)
The coronavirus (COVID-19) vaccine has become recently available, and to make vaccination campaigns successful, we should increase the acceptability of the COVID-19 vaccine within the public. Thus, this study has been conducted to provide insights into the factors affecting vaccine acceptance and pricing considerations. A both online and paperbased cross-sectional study was conducted from August 1 to August 30, 2020, among the general population of Pakistan. The health belief model (HBM) was used to assess predictors of the intent to receive the vaccine and the willingness to pay (WTP). Descriptive analysis was done, and a chi-squared test was used to assess the demographic association with HBM items. The majority (73.4%) showed a definite/probable intent to receive the vaccine, and marital status and education were significantly associated with getting the vaccine. WTP for a dose of the COVID-19 vaccine was highest for less than 1,000 Pakistani Rupees (PKR) and lowest for 10,001–20,000 PKR. This research indicates that the acceptability of the COVID-19 vaccine in the Pakistani community is satisfactory but the majority of the population want to spend less money to get immunized.
Keywords: Acceptability, COVID-19 vaccine, general public, Pakistan